Are employee-friendly workplaces conducive to innovation? - Chen, Jie; Leung, Woon Sau; Evans, Kevin P. (Journal of Corporate Finance, 2016)
We find strong evidence that firms with employee-friendly workplaces achieve greater innovative success, particularly in industries where innovation is more difficult to achieve. Furthermore, employee-friendly firms were also more inclined to sustain R&D investment during the recent crisis. These findings are consistent with the view that an employee-friendly workplace helps to develop tolerance for failure, which encourages engagement in innovation. We find no support for alternative explanations, such as employee-friendly workplaces helping to attract and retain talented employees and reducing career concerns of executives, which could nurture innovation.